2021
DOI: 10.5713/ajas.20.0336
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fermentation pattern and quality of Italian ryegrass (Lolium multiflorum Lam.) silage by wilting and inoculant treatments

Abstract: Objective: This study was conducted to investigate the effects of wilting and microbial inoculant treatment on the fermentation pattern and quality of Italian ryegrass silage.Methods: Italian ryegrass was harvested at heading stage and ensiled into vinyl bags (20 cm×30 cm) for 60d. Italian ryegrass was ensiled with 4 treatments (NWNA, no-wilting noadditive; NWA, no-wilting with additive; WNA, wilting no-additive; WA, wilting with additive) in 3 replications, wilting time was 5 hours and additives were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Moreover, plant cells remain active during the silage process, and the intracellular degradation enzymes degrade proteins to ammonia at low moisture contents [42]. This result was also demonstrated by Liu et al [43], who reported that in fresh ryegrass silage trials, lowering the moisture content led to a decrease in the CP content. The findings of Zheng and Fitzgerald et al [31,44] were also similar to the results of the present experiment.…”
Section: Effect Of the Mixing Proportion And Lactic Acid Bacteria Add...supporting
confidence: 54%
See 1 more Smart Citation
“…Moreover, plant cells remain active during the silage process, and the intracellular degradation enzymes degrade proteins to ammonia at low moisture contents [42]. This result was also demonstrated by Liu et al [43], who reported that in fresh ryegrass silage trials, lowering the moisture content led to a decrease in the CP content. The findings of Zheng and Fitzgerald et al [31,44] were also similar to the results of the present experiment.…”
Section: Effect Of the Mixing Proportion And Lactic Acid Bacteria Add...supporting
confidence: 54%
“…In this study, the LAB addition did not have a significant effect on DM. Liu et al [43] reported that the addition of Lactobacillus plantarum to Italian ryegrass silage had no significant effect on the dry matter content. Keady and Murphy's study also proved this point [47].…”
Section: Effect Of the Mixing Proportion And Lactic Acid Bacteria Add...mentioning
confidence: 99%
“…This change was similar to that observed in the F-FTMR with LP addition at 60 d of fermenting. Liu et al [38] who reported that the TDN of Italian ryegrass silage were lower than before ensiling. However, the TDN content treated MOL and LP exhibited higher TDN content in both of the FTMR.…”
Section: Chemical Composition Of Tmr After Fermentationmentioning
confidence: 98%
“…Crude protein and true protein were measured using a Kjeldahl nitrogen analyzer, while non-protein nitrogen was calculated by their difference [18]. After the reaction with anthrone, the content of WSC was determined via colorimetry [19]. In addition, the contents of neutral detergent fiber and acid detergent fiber were analyzed using an A220 fiber analyzer [20].…”
Section: Analysis Of Microbial Population Organic Acid and Chemical C...mentioning
confidence: 99%